Continuar inovando: Um projecto de reabilitação em Touguinhó - Pedro Miguel Barreiros da Costa (2020)
In this dissertation, entitled "continuar-inovando: um projeto de reabilitação em Touguinhó", we develop an investigation on the theme of rehabilitation, through the development of an architectural project for the rehabilitation of a house built in the 50s, in a small parish of Vila do Conde. This intervention in a real context provides a concrete case study, with which are associated specific problems that were the subject of the investigation and advised the development of the project. Thus, alongside the development of an actual project proposal for a real commissioned work, the necessary research that supports the ideas and the theoretical observations that constitutes the corpus of the Master's Thesis is developed. Finally, this opportunity also raises personal awareness and helps the development of a critical attitude as an architect, when facing the challenge of "building on the built".